2022
DOI: 10.1002/ecs2.3964
|View full text |Cite
|
Sign up to set email alerts
|

Floral turnover and climate drive seasonal bee diversity along a tropical elevation gradient

Abstract: The contribution of seasonality in species communities to elevational diversity of tropical insects remains poorly understood. We here assessed seasonal patterns and drivers of bee diversity in the Eastern Afromontane Biodiversity Hotspot, Kenya, to understand the contribution of seasonality to elevational biodiversity patterns. Bee species and plant species visited by bees were recorded on 50 study plots in regrowth vegetation across four major seasons along two elevation gradients from 525 to 2530 m above se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 80 publications
2
17
0
Order By: Relevance
“…Seasonality is known to shape the period of species occurrence and their interaction patterns. More so, a detailed seasonal turnover of bees and bee‐visited plant species has been reported for this region (see Dzekashu et al, 2022). Here, we observed an increase in nestedness with elevation, though it did not differ across seasons, following similar patterns of complete network interactions described above.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Seasonality is known to shape the period of species occurrence and their interaction patterns. More so, a detailed seasonal turnover of bees and bee‐visited plant species has been reported for this region (see Dzekashu et al, 2022). Here, we observed an increase in nestedness with elevation, though it did not differ across seasons, following similar patterns of complete network interactions described above.…”
Section: Discussionmentioning
confidence: 92%
“…We can argue this to be a result of reduced interdependence at higher elevations due to the increase in generality, hence the increasing connectance during the warm‐wet season (Classen et al, 2020). Moreover, the high seasonal turnover of species along these elevation gradients (Dzekashu et al, 2022) might prevent the aggregation of a more compact structure, hence the inconsistencies in observed connectance across seasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental factors played an important role in the response of indices, with a strong negative effect of temperature and rainfall seasonality on several indices. It has already been showed that seasonality strongly impacts diversity of communities in tropical terrestrial ecosystems (Correa et al, 2021; Dzekashu et al, 2022; Oita et al, 2021) but few studies highlighted such a result in lotic ecosystems, especially temperate (Epele et al, 2022; Li et al, 2019). Most studies in lotic ecosystems (Faulks et al, 2011) but also in other ecosystems highlighted the predominance of environmental factors such as altitude or temperature seasonality (Howard et al, 2019).…”
Section: Discussionmentioning
confidence: 99%